Study to Determine the Optimum Method in Writing a CNC Milling Program for a Specific Product - Muhammad Marsudi (AL-JAZARI JOURNAL SCIENTIFIC OF MECHANICAL ENGINEERING, 2016)
The trend towards automation of production equipment is having great demands from people. Since the early 1970s, manufacturers have worked to increase productivity, quality, process capability, reliability and flexibility. They used technologies to improve quality and productivity. This study studies the differences of a few CNC milling program – relating to time scale and machining accuracy. For experiment, a few programs are being written to machining a simple product. Each program has its own features. By running all the written programs, the effectiveness and goodness of each program could be analyzed. On the other hand, by machining the product and testing them, the product accuracy also can be analyzed. The results show that, the number of command lines will affect the simulation time. More command lines in the program will need more time in running the simulation. Besides that, results show that using the Canned Cycle command will give a more accurate machining compared to those conventional and CAD/CAM method